Órgão de solução de controvérsias da Organização Mundial do Comércio: uma análise de sobrevivência dos países-membros aos contenciosos no período de 1995 a 2018 - Carvalho, Samuel Rufino de (2019)
The Dispute Settlement Body (DSB) of the World Trade Organizations (WTO) is the main instrument through which member states stake their claims. The organization is an assertive reflection of the International Trade Regime (ITR). In this respect, this dissertation aims at analyzing whether the level of development of a member state affects its participation in the DSB, impacting on the effectiveness of the ITR in solving two problems of the international trade system: protectionism and the obstacles to development. For this purpose, the Simple Effectiveness (SE) of International Regimes was utilized as theoretical framework. The Survival Analyses was used as methodology. It focuses on the time until the occurrence of an event of interest. Therefore, the events analyzed were the complaints and responses before the DSB. Two different tools were used. First, the Kaplan-Meier Curve, which indicates the survival time of an individual until the occurrence of an event, was plotted. Thereafter, the Cox Regression was used. This tool associates the Survival Analyses to linear regression in order to examine the impacts of some independent variables (IVs) on the time until the occurrence of the events observed. The results showed that states with higher levels of Gross Domestic Product (GDP) and Human Development Index (HDI), and with bigger population have more chances of initiating a dispute and being questioned. Likewise, the American and the European continents are more likely to experience these events. In respect to the status of development, it was perceived that developed countries (DC) and developing countries (DCs) experience the incidence of an event more easily when compared to least developed countries (LDC). Regarding the variables related to the disputes, no set of characteristics could satisfactorily explain the occurrence of the events. As final thoughts, it was noted that the ITR is not able to reach complete effectiveness due to the lack of consensus among member states concerning the issue to be solved by the Regime.